2021
DOI: 10.1002/suco.202000729
|View full text |Cite
|
Sign up to set email alerts
|

The deflection of reinforced concrete beams containing recycled steel fibers

Abstract: A 3-stage model is used to evaluate the results of an experimental campaign, previously carried out with the aim of studying the deflection of reinforced concrete structures made with reinforced concrete (RC) and fiber-reinforced concrete (R/FRC). In particular, 12 four-point bending tests were performed on beams, whose cross-sections were obtained by combin-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[22][23][24] It is worth mentioning industry uses high-strength steel wires for tire production, so the quality of steel fibers recovered from waste tires is superior to standard industrial fibers available in the market (recycled steel fibers have more ductility and higher tensile strength than steel fibers). [25][26][27] Since recycled steel fiber concrete is made of different ingredients (i.e., cement, water, fine and coarse aggregate, and fiber), the weight percentage of each ingredient influences the mechanical properties of fresh and hardened concrete. Table 1 summarizes previous research conducted on steel fiber reinforced concretes, including the percentage of fiber and resulting optimum fiber value (per unit weight), used steel fiber type, and type of performed mechanical tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] It is worth mentioning industry uses high-strength steel wires for tire production, so the quality of steel fibers recovered from waste tires is superior to standard industrial fibers available in the market (recycled steel fibers have more ductility and higher tensile strength than steel fibers). [25][26][27] Since recycled steel fiber concrete is made of different ingredients (i.e., cement, water, fine and coarse aggregate, and fiber), the weight percentage of each ingredient influences the mechanical properties of fresh and hardened concrete. Table 1 summarizes previous research conducted on steel fiber reinforced concretes, including the percentage of fiber and resulting optimum fiber value (per unit weight), used steel fiber type, and type of performed mechanical tests.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcing capability of these fibers makes them prominent as one of the practical solutions for improving the hardened properties of the concretes 22–24 . It is worth mentioning industry uses high‐strength steel wires for tire production, so the quality of steel fibers recovered from waste tires is superior to standard industrial fibers available in the market (recycled steel fibers have more ductility and higher tensile strength than steel fibers) 25–27 …”
Section: Introductionmentioning
confidence: 99%
“…The behavior of fiber reinforced concrete (FRC) at the serviceability limit state has received much less research attention than at the strength limit state. Relative to RC, FRC members typically display reductions in crack spacings 1,2 and crack widths, 3,4 as well as improvements in member stiffness 5–7 and reductions in instantaneous 8,9 and long‐term (LT) deformations and crack widths 4,10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Recent research revealed that steel fibers originating from the waste tire recycling industry could be a helpful reinforcement system to significantly reduce cementbased materials' brittle behavior. [31][32][33][34][35][36][37] Using recycled materials can help solve the pollution caused by industrial development, which has severe and irreparable consequences on the environment, in addition to reducing the production costs of fiber reinforced concrete. One of the originalities of this research is using the low-cost and eco-friendly tire-recycled steel fiber.…”
Section: Introductionmentioning
confidence: 99%